CEO Characteristics, Family Ownership and Corporate Social Responsibility Reporting: The Case of Saudi Arabia - Shaker Dahan AL-Duais (MDPI AG, 2021)
Only a few studies have investigated the association between the characteristics of the chief executive officer (CEO) (i.e., tenure and local or expatriate) and corporate social responsibility (CSR) reporting. Our study adds to the fledgling literature by providing new evidence from Saudi Arabia. Given the dominance of family control among Saudi Arabian listed firms, additionally, this study examined the moderating effect of family ownership on the CEO-CSR relationship. Using CSR scores from Bloomberg database from 2010 to 2019 and ordinary least squares (OLS) regression, the findings reveal that the association between CEO tenure and CSR reporting is positively significant; however, the association between CEO nationality and CSR is not significant. In addition, the findings indicate that family ownership is an important contingency factor that explains the association between CEO tenure and CEO nationality, and CSR reporting. Our study contributes to an emerging line of CSR research that investigates the effects of foreign CEOs on CSR transparency, and supports prior evidence on the benefits to investors of having long-serving CEO and the costs of family entrenchment.